The importance of bites by the saw-scaled or carpet viper (Echis carinatus): epidemiological studies in Nigeria and a review of the world literature. - Warrell, D; Arnett, C (1976)
The incidence of Echis carinatus (saw-scaled or carpet viper) bite and its mortality have been investigated in the Nigerian savanna region. A geographical area was defined in which the snake was particularly abundant and bites were frequent. Perennial and seasonal fluctuations in incidence and mortality, the circumstances in which bites occurred and the types of people bitten were studied at Bambur, Zaria, Kaltungo and Gombe hospitals. Peak incidence coincided with the increase in farming during the rains whereas percentage mortality seemed to be greatest during the cold dry season. The majority of the patients were young males bitten on the foot while walking or farming. A review of the world literature indicated that E. carinatus was the principal cause of snake bite morbidity wherever data were available throughout its wide geographical range. Official statistics have seriously underestimated this important rural health problem.